2022
DOI: 10.1097/md.0000000000029511
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory clinical trial to evaluate the efficacy and safety of carbon dioxide paste in healthy people

Abstract: Introduction: Scarring and pain are postoperative complications in patients after head and neck cancer treatment; however, there is no effective treatment. These complications are affected by local blood flow disorders, and it is well known that the transcutaneous application of carbon dioxide (CO2) improves local blood flow. Previously, we have shown that the transcutaneous application of carbon dioxide causes absorption of CO2 and increase the oxygen (O2) pressure in the treated tissue; it is expected that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In addition, patients with a vomiting reflex or limited mouth opening have difficulty receiving CO 2 . To overcome these problems, we have developed a CO 2 paste that does not produce gaseous CO 2 and is efficiently absorbed by the skin [46]. In the future, we hope to clarify the efficacy of this paste in inhibiting HNCs progression.…”
Section: Plos Onementioning
confidence: 99%
“…In addition, patients with a vomiting reflex or limited mouth opening have difficulty receiving CO 2 . To overcome these problems, we have developed a CO 2 paste that does not produce gaseous CO 2 and is efficiently absorbed by the skin [46]. In the future, we hope to clarify the efficacy of this paste in inhibiting HNCs progression.…”
Section: Plos Onementioning
confidence: 99%
“…Oe et al demonstrated similar changes to those that occur within muscles when aerobic exercise is performed [ 23 ]. And we have shown that the transcutaneous application of CO 2 to the human neck and lower extremities can improve blood flow [ 17 ]. However, the effect of transcutaneous application of CO 2 on cancer-related skeletal muscle atrophy is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) therapy is widely known as an effective treatment to improve blood flow and has been indicated for various diseases such as heart disease and skin conditions [ 16 ]. We demonstrated that transcutaneous application of CO 2 could improve local blood flow and promote the suppression of muscle atrophy and contraction, as well as the recovery of muscle damage [ 17 23 ]. However, while we have demonstrated the effect of transcutaneous application of CO 2 in suppressing tumor growth [ 24 ], we have not demonstrated the effect of cancer cachexia.…”
Section: Introductionmentioning
confidence: 99%
“…In a phase 1 clinical study, we reported that CO 2 paste application increases blood flow to the skin and muscles without any side effects [ 26 ]. Since transcutaneous CO 2 application induces angiogenesis by inducing an artificial Bohr effect, we hypothesize that this simple and adaptable treatment can alleviate side effects and improve the QOL of patients undergoing neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method uses CO 2 gas, which is difficult to apply to the head and neck. In a recent study, we investigated the usefulness, safety, and feasibility of a CO 2 paste by analyzing the changes in blood flow in a phase 1 clinical study in healthy individuals [ 26 ]. The CO 2 paste reacted with water on the skin surface, could infiltrate CO 2 transcutaneously without the use of external CO 2 gas, and could be applied to the head and neck region.…”
Section: Introductionmentioning
confidence: 99%